PENINGKATAN KETERAMPILAN MENULIS ESAI BAHASA INDONESIA MELALUI STRATEGI PEMODELAN - Ade Eka Anggraini; Elih Solihatulmilah (JURNAL PENDIDIKAN DASAR SETIA BUDHI (JPDS), 2020)
The research aims at improving students’ essay writing competence through Modeling Strategy at SDN 3Rangkasbitung Lebak Banten.The study employed Action Research conducted in two cycles. In collecting thedata, the writer used essay writing test, questionnaire, interview, document and observation as well.Moreover, in analyzing the data the descriptive statistics was utilized. The data were analyzed bothqualitatively and quantitatively. The research findings show that Modeling Strategy is effectively improvedstudents’ essay writing competence. As shown from the preliminary test result dealt with students’ essaywriting competence on 41 students at the cycle I. There was no student with very high competence, 2 studentsgood competence (4.9%), 34 students medium competence (82, 9%), and 5 students low competence (12,2%). Then, on cycle II became 13 Students (31, 7%) with very good competence, 28 students (68, 3%) withgood competence, and no more students with medium and low competence.Keywords: teaching and learning, essay writing, Modeling Strategy.AbstrakTujuan utama penelitian ini adalah untuk menjelaskan proses pembelajaran dan hasil proses peningkatanketerampilan siswa dalam menulis esai bahasa Indonesia melalui strategi pemodelan. Penelitian ini dilakukandi SDN 3 Rangkasbitung Lebak Banten. Penelitian ini menggunakan studi penelitian tindakan dengan duasiklus. Teknik analisis datanya menggunakan statistic deskriptif. Data penelitian ini berupa tulisan esai, hasilangket, hasil wawancara, dokumen dan hasil observasi. Hasil pengumpulan data diolah secara kualitatif dankuantitatif. Dari data tersebut diperoleh hasil pembelajaran menulis bahasa Indonesia siswa SDN 03Rangkasbitung dengan menggunakan strategi pemodelan. Dari 41 siswa saat tes awal tidak ada siswa yangbertingkat sangat baik, setelah tindakan tes akhir siklus II menjadi 13 siswa (31,7%). untuk skor baik tes awalterdapat 2 siswa (4,9%) meningkat menjadi 28 (68,3%). Untuk skor sedang awal terdapat 34 siswa (82,9%)menjadi tidak ada. Untuk skor kurang terdapat 5 siswa (12,2%) meningkat menjadi tidak ada.Kata kunci: Pembelajaran, Menulis Esai, Strategi Pemodelan